2014
DOI: 10.5897/ajar12.2241
|View full text |Cite
|
Sign up to set email alerts
|

Effect of enriched farmyard manure and inorganic fertilizers on grain yield and harvest index of hybrid maize (bh-140) at Chiro, eastern Ethiopia

Abstract: Application of farmyard manure (FYM) alone or in combination with inorganic fertilizers helps in proper nutrition and maintenance of soil fertility in maize fields when applied at proper doses replenishing the most deficient macro and micro nutrients which in turn help in getting the highest grain yield and harvest index in hybrid maize varieties. The harvest index determines how many photosynthates are transformed into economic yield. It is the ratio of economic yields to biological yield. A study was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
2
5
0
Order By: Relevance
“…This underscores the fact that the applied fertilizers were highly mineralized such that the uptake was efficiently metabolized into kernel yield better than development of morphological attributes. Similar view had been shared by Uwah et al [ 44 ] on sweet maize and Bekeko [ 45 ] on hybrid corn in eastern Ethiopia.…”
Section: Discussionsupporting
confidence: 79%
“…This underscores the fact that the applied fertilizers were highly mineralized such that the uptake was efficiently metabolized into kernel yield better than development of morphological attributes. Similar view had been shared by Uwah et al [ 44 ] on sweet maize and Bekeko [ 45 ] on hybrid corn in eastern Ethiopia.…”
Section: Discussionsupporting
confidence: 79%
“…This might be due to the depletion of plant nutrients in the soil. In line with these results, Abebe et al (2013) reported yield reduction in continuous mono‐cropping of maize as compared with the effect of precursor crops. On the other hand, the yield of maize rotated with soybean showed a permanent trend across cropping seasons.…”
Section: Discussionmentioning
confidence: 56%
“…Improved varieties are also associated with increased efficiency of fertilizer use relative to local varieties (Vanlauwe et al, 2011). Several factors-for example, poor agronomic practices, including low use of inputs (Agegnehu et al, 2016;Zelalem, 2014;Bekeko, 2013)-besides outdated varieties (Shiferaw et al, 2014) are argued to be responsible for low yields observed in farmer fields. Yet, inappropriate plant densities appear to be the most important factor at the studied sites.…”
Section: Discussionmentioning
confidence: 99%